Efektivitas Pupuk Organik Cair Jerami Padi dan Ampas Teh Terhadap Pertumbuhan dan Kandungan Kalsium Tanaman Selada (Lactuca sativa L.) - Pujiati Pujiati; Aminah Asngad (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine differences in growth and calcium levels of lettuce plants ( Lactuca sativa L.) after applying liquid organic fertilizer from rice straw and tea dregs. This research used an experimental method with a Completely Randomized Design (CRD) with 3 replications and two factors, namely the dose of liquid organic fertilizer (P1 = 10 ml and P2 = 13 ml) and the time of application of liquid organic fertilizer (W1 = once every 5 days and W2 = every 7 days). The results of the research showed that all treatments had different effects on the growth and levels of lettuce plants. The treatment that has the most influence on the growth and calcium levels of lettuce plants is P2W2 (13 ml fertilizer dose and application time every 7 days). Keywords: Tea dregs, rice straw, calcium, lettuce plants, liquid organic fertilizer